THE CORRELATION BETWEEN THE FEEDING PATTERNS AND THE STUNTING PREVALENCE IN TODDLERS AGED 24-59 MONTHS IN THE WORKING AREA OF LUMBI-LUMBIA HEALTH CENTER - Lubis, Dina Putri Utami; Ludong, Rian (Universitas Respati Yogyakarta, 2021)
Background: Stunting is one of the nutritional problems occurring in Indonesia. It had an impact not only for those who experiences it but also for the economy and development of the country. Human resources with stunting have lower quality than the normal one. Based on data from the World Health Organization (WHO) in 2017, Indonesia was in the fourth position with the highest prevalence of stunting in the world. Research Objectives: To determine the relationship between feeding patterns and the prevalence of stunting in toddlers aged 24-59 months in the working area of â€‹â€‹Lumbi-lumbia Health Center. Research Methods: This type of research was quantitative using an analytical survey with a cross sectional approach. The population in this study were 118 parents who had stunted toddlers aged 24-59 months with the sample of 95 respondents who were taken based on purposive sampling technique. The data was collected using a questionnaire on feeding patterns and toddlers, the data was measured using microtoise and then was converted into a standard value (z-score). The data analysis used chi square test with a significant Î± = 0.05. Research Results: The results showed that the respondent's inappropriate feeding pattern was 71.60% and the right feeding pattern was 28.40%. While the prevalence of stunting in the short category was 73.70% and the one in the very short category was 26.30%. Conclusion: There is a relationship between the feeding patterns and the prevalence of stunting in toddlers aged 24-59 months in the working area of â€‹â€‹the Lumbi-lumbia Health Center with Ï value of 0.034. Keywords: stunting; feeding pattern; toddler